Determinants of optimal capital structure for non-financial firms listed on the JSE - Chipeta, Chimwemwe (University of the Witwatersrand, Johannesburg, 2024)
This paper investigates the determinants of optimal capital structure while considering the influence of the cost of capital, specifically examining the relationship between firm-specific variables known to drive optimal capital structure (such as firm size, asset tangibility, growth, liquidity, and profitability) and the cost of capital. The analysis of these determinants in developing countries is intriguing due to the differences in firm characteristics compared to those in advanced economies. The study utilizes primary data sourced from Refinitiv Workspace for 189 firms across various sectors listed on the Johannesburg Stock Exchange (JSE) from 2015 to 2023, excluding financial services and insurance sectors. Panel econometric approaches, including Feasible Generalised Least Squares (FGLS) and the Generalised Method of Moments (GMM) regression method, are employed for analysis. The findings of the study unveil several noteworthy relationships between independent variables and the Weighted Average Cost of Capital (WACC). Firm size, profitability, asset tangibility, and growth emerge as key determinants affecting WACC to varying degrees. Firm size and profitability exhibit positive associations with WACC, supported by statistically significant coefficients. This implies that increases in firm size and profitability correspond to higher WACC levels. Conversely, asset tangibility and growth demonstrate negative correlations with WACC, backed by statistically significant coefficients. Furthermore, firm size and profitability maintain their positive relationships with WACC across various estimation models, including Feasible Generalized Least Squares (FGLS) and Generalized Method of Moments (GMM). This consistency underscores the robustness of these relationships, with larger and more profitable firms consistently exhibiting higher WACC.
A research report submitted in fulfillment of the requirements for the Master of Commerce, In the Faculty of Faculty of Commerce, Law and Management, School of Economics and Business Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; firm size; asset tangibility; growth; liquidity; profitability; cost of capital; capital structure; SDG-8: Decent work and economic growth